Determine concentration radon 222Rn in the air inside and outside the buildings at the summer and winter in the province of Baghdad - Neshaat R. Al-Ataby; Basem, H. Aisa; Hadi, M. Jebir; Jifer, N. Hatem (Journal of Madenat Alelem University College, 2010)
In this study, Was use of solid-state nuclear track detectors in the measurement of concentrations of radon (222Rn) inside and outside of the buildings in the summer and winter of the Baghdad province and because of the high features of the technical sensitivity and efficiency to record track of charged particles (such as protons and alpha particles and fission fragments) . Is the radon of Environmental Pollutions that is caused health problems , that was seemed the concern at the problem of pollution, radon gas (222Rn) and thoron gas (220Rn) and the considerable risk resulting from exposure to these isotopes by alpha particles emitted which have proved the relationship between exposure to emitted alpha particles with the incidence of disease of lung cancer. In this study, measured the concentration of radon (222Rn) inside and outside buildings in the summer and winter in several areas from the Baghdad province and as showed in the attached tables. Been studied the environmental radioactivity and measurement of the concentration of radon gas in the air in different parts of the city of Baghdad. the highest concentration was Found in the second Orfali (A) (of the Sadr City) for the summer and was (37.973 Bq/m3) outside the building and ((53.400 Bq/m3 inside the building, either for the winter season was (55.773 Bq/m3) outside the building and (Bq/m3 58.148) inside the building for the same region and This is the concentration within the limits allowed